Harmony of Chinese Cultural Acculturation in the Aesthetic Perspective of Art Anthropology in Surakarta - Achmad Nur Kholis; Norhayati Ayob (Gondang: Jurnal Seni dan Budaya, 2025)
Surakarta is the center of Javanese culture in Indonesia. Many kinds of arts and culture have not been studied in depth, one of which is the phenomenon of cultural acculturation. The arrival of foreign countries to Indonesia influenced the unification of cultures that created new cultural forms. There are several ethnicities and races that live and settle in this area that influence the creation of new cultures, one of which is the Chinese people who come from China. Every year the Chinese and the general public hold a joint Chinese New Year celebration centered on Pasar Gede Hardjonagoro. The relationship that occurs in the ceremonial is a potential to get findings about the harmony of cultural acculturation that occurs from this phenomenon. The research method used is a descriptive qualitative type as an effort to present naturalistic data in the field in the form of sentences. There are several techniques applied in the data collection process, namely observation, interviews, and documentation. The application of the three techniques is based on the suitability of the topic and is supported by an approach in the form of theory. The approach comes from the theory of art anthropology proposed by Ruth Bunzel. The relationship between people, culture, and art occurs in harmony in Surakarta City. One place that has become a cultural center in the city of tolerance is Pasar Gede Hardjonagoro. The traditional market is one proof of the harmony of Chinese and Javanese cultural acculturation that goes hand in hand. The Chinese New Year celebration is a ceremonial example that can be followed by the whole community, without any special attention to the background. This cultural acculturation is a step to maintain tolerance in the community.